Cultural Images of the East and West in Elif Shafak's Novels - Mihaela Ichim (Linguaculture, 2022)
This article is intended to discuss the images of the East and West as they are portrayed in Elif Shafak’s novels, with emphasis on the ethnic cliches and stereotypes which are often engendered in and disseminated through fiction. More specifically, it examines how the novelist depicts Turkish and Oriental culture, often in contrast with its Western counterpart, through the complex and insightful images she skillfully creates. The theoretical part of the article relies on the seminal works of imagologists such as Joep Leerssen and Manfred Beller, who have laid the foundations for the study of cultural images, with emphasis on their shifting, dynamic and context-dependent nature, as well as on David Katan’s logical levels of culture, which are used as a starting point for the analysis of the similarities and differences between the East and the West as represented in Shafak’s work.